Kompetensi Kepribadian Guru Perspektif Al-Qur’an Surah Al-Hujurat Ayat 13 Kajian Ilmu Pendidikan Islam - Sulaiman, Husnan; Najib, M Rizky Ainun (STAI Al-Musaddadiyah Garut, 2025)
Personality competence is one of the four teacher competencies and cannot be separated from other competencies, which are contained in the Indonesian law No.14 of 2005, namely pedagogical competence, social competence, and professional competence. This competency is a set of knowledge, skills, and behaviors that must be owned, lived and mastered by the teacher and has become part of him to carry out his professional duties. In the Qur'an surah Al-Hujurat verse 13, the teacher's personality and values are in line with the purpose of Allah SWT to create humans from different individuals to create harmony in life and get to know each other among them. The purpose of this study is to describe it: 1) Competence of teacher personality in Islamic Education. 2) Competence of teacher personality perspective of the Qur'an surah Al-Hujurat verse 13. 3) Implementation of teacher personality competence perspective of the Qur'an surah Al-Hujurat verse 13. This research uses a type of literature review with the method used is the library study method (library research). The literature study method is a method of collecting data by understanding and studying theories from various literatures related to the research. The data sources used in this study consist of primary sources; namely the Al-Qur'an surah Al-Hujurat verse 13, and secondary sources; namely books, books, and other references that can support this research. The results of this study indicate that the teacher's personality competence from the perspective of the Qur'an surah Al-Hujurat verse 13 consists of several values which include: gender equality, applying tolerance behavior, piety to Allah SWT Therefore, research on the teacher's personality competence contained in Al-Quran Surah Al-Hujurat verse 13 specifically shows the importance of respecting and understanding diversity as a manifestation of the existence and nature of human life. Thus the results of this research are presented as authentic scientific findings. Keywords : Islamic Education Science, Teacher Personality Competence, Qur'an Surah Al-Hujurat Verse 13